Dropephylloidea, a remarkable new genus from south Europe and the Middle East (Coleoptera: Staphylinidae: Omaliinae: Omaliini) - Shavrin, Alexey V. (Zootaxa, 2025)
A new omaliine genus, Dropephylloidea gen. n. is described. Morphologically, the new genus is related to Dropephylla Mulsant & Rey, 1880 and Phyllodrepa Thomson, 1859, but differs from them by the proportions of maxillary palpomeres and gonocoxites of the female genital segment, the shape of the modified and extremely elongate metatrochanter of the male, and the unusual external and internal structure of the aedeagus. The new genus includes one species, D. curticollis (Eppelsheim, 1889) comb. n. (from Dropephylla), distributed in southern Europe (Albania, Croatia and Italy) and the Middle East. The species is redescribed and illustrated, and a distributional map is provided. A lectotype for Homalium (Phyllodrepa) curticolle Eppelsheim, 1889 is designated. The main morphological features of the new genus and its taxonomic relationship with other related genera of Omaliini MacLeay, 1825 are briefly discussed. Dropephylloidea curticollis is recorded from Albania, Croatia, Israel and Italy for the first time. In addition, an erratum is provided: Dropephylla ivani nom. n. is proposed as a replacement name for D. loebli Shavrin, 2024: 592, a junior primary homonym of D. loebli Thayer, 2003: 323.